Effectiveness of short duration phototherapy in government hospital setup - Bhosgi, Revanasiddappa; Harwalkar, Kirankumar (International Journal of Contemporary Pediatrics, 2021)
Background: Neonatal hyperbilirubinemia is most common presentation of neonates. Phototherapy remains standard treatment for neonatal hyperbilirubinemia. Overcrowding in government hospital makes it difficult to give phototherapy for more than 1-2 days. The objectives of the study were to determine the effectiveness of short duration of phototherapy in treating hyperbilirubinemia and to determine the risk of rebound hyperbilirubinemia. Methods: Study was hospital based retrospective study. The study place was GIMS kalaburagi. The study was conducted from September 2019 to December 2019. All healthy full-term neonates with serum bilirubin above cut off range according to (American academy of pediatrics) nomogram were included in the study. Requirement of phototherapy was decided on serum bilirubin levels as per AAP (American academy of pediatrics) nomogram. Phototherapy was used as treatment modality. Results: Total 110 neonates were included in the study. Total of 56 neonates (50.9%) required 1 day of phototherapy to fall within normal limits for discharge and 46 neonates (41.8%) required 2 days of phototherapy to fall within normal limits for discharge with a significant p<0.05. Rebound hyperbilirubinemia requiring repeat phototherapy was seen in 6(10%) neonates who were discharged after 1 day of phototherapy and in 5 neonates (10%) who were discharged after 1 day of phototherapy with a p value of 0.05. Conclusions: Short duration phototherapy is the effective means of treatment for most neonates in government hospital set up. Serum bilirubin has to be reviewed during follow up to assess rebound hyperbilirunemia.